Our HER2 is same as yours - Song, Haa-Na; Park, Se Hoon (Translational Gastrointestinal Cancer; Vol 4, No 6 (November 16, 2015): Translational Gastrointestinal Cancer (Revisiting Robotic Surgery for Stomach), 2015)
Despite its declining incidence, gastric cancer remains the third most common cancer worldwide (1), with the highest incidence in East Asian and the lowest in North America (2). As compared to non-Asians, although this may represent more than a few different clinical presentations between ethnicities, Asian gastric cancer patients consistently have increased survival rate (3). The ethnic differences might be due to a chance or different tumor biology between Asian and Western patients, or to a different pharmacogenomics in drug metabolism leading to a different drug exposure. The disparity between Asian and non-Asian gastric cancer survival is not explained by the hypothesis of differences in tumor biology (4), in which Asian ethnicity was not independently associated with survival [hazard ratio (HR) 0.89; 95% confidence interval (CI) 0.74-1.08] if adjusted for other patient and disease characteristics.